Interaction of Human Dopa Decarboxylase with L-Dopa: Spectroscopic and Kinetic Studies as a Function of pH. (26th May 2013) - Montioli, Riccardo; Cellini, Barbara; Dindo, Mirco; Oppici, Elisa; Voltattorni, Carla Borri
Abstract : Human Dopa decarboxylase (hDDC), a pyridoxal 5′-phosphate (PLP) enzyme, displays maxima at 420 and 335 nm and emits fluorescence at 384 and 504 nm upon excitation at 335 nm and at 504 nm when excited at 420 nm. Absorbance and fluorescence titrations of hDDC-bound coenzyme identify a single pK spec of ~7.2. This pK spec could not represent the ionization of a functional group on the Schiff base but that of an enzymic residue governing the equilibrium between the low- and the high-pH forms of the internal aldimine. During the reaction of hDDC with L-Dopa, monitored by stopped-flow spectrophotometry, a 420 nm band attributed to the 4′-N-protonated external aldimine first appears, and its decrease parallels the emergence of a 390 nm peak, assigned to the 4′-N-unprotonated external aldimine. The pH profile of the spectral change at 390 nm displays a pK of 6.4, a value similar to that (~6.3) observed in both k cat and k cat / K m profiles. This suggests that this pK represents the ESH + → ES catalytic step. The assignment of the pKs of 7.9 and 8.3 observed on the basic side of k cat and the PLP binding affinity profiles, respectively, is also analyzed and discussed.